Meningkatkan Mahārah Al-Kitābah Dengan Pembelajaran Kaligrafi - Mario Bagus Sanjaya; Aqila Aqila; Nurul Huda Hasibuan; Sakholid Nasution (CV. ALIM'SPUBLISHING, 2025)
This research aims to improve students' Mahārah Al-Kitābah (writing ability) through learning calligraphy. The problem raised was the low writing skills of students in elementary schools, which had an impact on their ability to convey ideas and information effectively. This research used an experimental method with a pre-test and post-test design, involving two groups of students: one group who were taught to write using calligraphy techniques and a control group who followed conventional learning. Research findings showed that the group that received calligraphy learning experienced significant improvements in Mahārah Al-Kitābah compared to the control group. The average post-test score of the calligraphy group increased by 30% compared to the pre-test, indicating the effectiveness of this method in improving writing skills. The implications of this research indicate that integrating calligraphy learning in the curriculum can be an effective strategy for improving students' writing skills, as well as fostering their interest and love for the art of writing. In addition, the results of this research can be a reference for educators in designing more innovative and interesting teaching methods to improve Arabic language skills in schools.